THE POLITICS OF PRONOUNS: TRANSLATING GENDER IDENTITY IN LANGUAGES LIKE HINDI/MARATHI IN INDIA - Bonsale, Gajanan; Shah, Dr. Roopa; Dudhate, Madhav; Sarda, Shweta; Undare, Raghunath (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research paper explores the intricate politics of pronoun translation within India's diverse linguistic and cultural landscape, focusing on the complexities of gender identity. Translating gender-neutral or non-binary pronouns in Indian languages like Hindi and Marathi presents unique challenges due to their rich pronoun systems, which convey social hierarchy, respect, and kinship. The paper examines how these nuanced pronouns are navigated in translation, especially into languages like English, which often lack equivalent distinctions. Through studies of literary works and real-world examples, the research delves into how pronoun translation intersects with broader issues of gender inclusivity, social justice, and the evolving recognition of non-binary identities in India. It highlights the socio-political implications of linguistic choices and the need for translators to balance accuracy with cultural sensitivity. By addressing these challenges, the paper contributes to discussions on fostering inclusivity and equity in language practices while respecting the complexities of India’s multilingual and multicultural context.